Screening of ridge gourd varieties for resistance to root-knot nematode, Meloidogyne incognita - Shobha, G; Kantharaju, V (Indian Journal of Plant Protection, 2020)
Root-knot nematode, Meloidogyne incognita is a major pest on ridge gourd and causes considerable yield losses by causing extensive root damage resulting in serious economic losses. Screening of 15 ridge gourd varieties was carried out against M. incognita to identify resistance sources. Gall formation was examined on ridge gourd roots inoculated with second stage juveniles of the nematode and using the gall index (GI), varieties were categorized as resistant or susceptible. Out of 15 tested ridge gourd varieties, two varieties viz., Arka Sumeet and Arka Sujat (GI 2.0 to < 3.0) were found to be resistant, six viz., R G Anjali, RNR, Ridge gourd Agri JHL-12, JK SPL, Pusa Nasdar and Padmini (GI 3.0 to < 4.0) were moderately resistant, five varieties viz., Sarpan F1 hybrid RG-33, US- 6001, Ridge gourd JPL, Narayana and Indam 1222 (GI 4.0 to < 5.0) were found to be susceptible and remaining two Ridge gourd PN and Jaipur Long (GI = 5.0) were found to be highly susceptible.